351 Informal Caregivers with Insomnia May Benefit From an Insomnia Treatment Using an Acceptance and Commitment Therapy Approach. (3rd May 2021) - Song, Yeonsu; McGowan, Sarah Kate; Kelly, Monica; Carlson, Gwendolyn; Fung, Constance; Josephson, Karen; Zeidler, Michelle; Alessi, Cathy; Martin, Jennifer
Abstract: Introduction: Insomnia among informal caregivers (providing care to family/friends) is common and associated with worse mental and physical health outcomes. Traditional cognitive behavioral therapy for insomnia may be challenging for caregivers whose beliefs about sleep may relate to beliefs and behaviors that are intertwined with their unique situation of caregiving. We examined whether an insomnia treatment using an acceptance and commitment (ACT) approach (i.e. committing to values-based actions toward goals vs. experiential avoidance of distressing emotions/thoughts) plus sleep restriction, stimulus control and sleep hygiene improves sleep, mental health, and daytime symptoms among caregivers. Methods: We analyzed data from women veterans with insomnia who were informal caregivers (mean age=44 years [range 25–57]; N=6) and were participating in a clinical trial of an ACT-focused treatment (termed ABC-I). We measured: Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Patient Health Questionnaire (PHQ-9), General Anxiety Disorder (GAD-7), 11 items assessing symptoms of daytime impairment due to poor sleep derived from the International Classification of Sleep Disorders-Third Edition, and the Acceptance and Action Questionnaire (AAQ). Student t-tests were used to compare outcomes between pre- and post-ABC-I. Results: Caregivers showed significant improvements between pre- and post-ABC-I (all p-values<0.05) in the following outcomes: ISI (14.3±5.4 vs. 3.8±3.2), PHQ-9 (9.8±7.2 vs. 2.8±3.8), GAD-9 (9.0±6.6 vs. 2.0±1.8), and number of symptoms of sleep-related daytime impairment (6.8±4.0 vs. 3.8±3.5). Caregivers also showed improvement trends in PSQI (10.0±4.1 vs. 5.2±1.2, p=0.06) and AAQ score (24.0±12.7 vs. 16.2±8.0, p=0.05). Conclusion: We found that caregivers with insomnia may benefit from ACT-based treatment in improving perceived sleep quality and insomnia, depression, anxiety, sleep-related daytime impairment and reduced experiential avoidance. This approach may increase motivation by linking the sleep program to core values, and acceptance and tolerance of emotions or thoughts may benefit caregivers with insomnia. Further studies using an ACT-based insomnia program are needed to test its effect in a larger sample of caregivers and evaluate benefits in terms of reduced stress and improved health. Support (if any): VA HSR&D (Martin IIR 13-058-2 and RCS-20–191), NIA (K23AG055668, Song), NHLBI (K23HL143055, Martin) of the NIH, VAGLAHS GRECC, and VA Office of Academic Affiliations (Kelly; Carlson).